A Note on Skew Derivations and Antiautomorphisms of Prime Rings - Faez A. Alqarni; Nadeem U. R. Rehman; Hafedh Alnoghashi; Junaid Nisar; Omar Al-Mallah (Journal of Mathematics)
In this article, we investigate the behavior of a prime ring which admits a skew derivation satisfying certain functional identities involving an antiautomorphism. We employ tools such as generalized identities and commutativity-preserving maps to analyze these rings. Furthermore, examples demonstrate that the conditions imposed on the hypotheses are essential.